Goldenhar syndrome (Anwer Khan Modern Medical College Journal, 2021)
Goldenhar Syndrome or Oculoauriculovertebral Syndrome is a complex syndrome characterized by an association of maxillomandibular hypoplasia, deformity of the ear, ocular dermoid and vertebral anomalies and the most severe form of hemifacial microsomia. Here we describe a 12 years female patient with Goldenhar Syndrome came to Ophthalmology department at Anwer Khan Modern Medical College & Hospital.AKMMC J 2022; 13(1) : 60-64